IMPROVEMENT OF HYDRAULIC MODEL OF WATER FLOW DYNAMICS IN KATA FERGONA MAIN CHANNEL - Ilkhomjon Ernazarovich Makhmudov; I. Kh. Takhirov; Uktam Temirovich Jovliyev; Narziev Jasurbek Juraevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The hydraulic model of the water flow dynamics of the Great Fergana Main Canal was improved and the influence of the damping (support) formation of the water flow in the hydraulic structure was clarified based on this model. Now, the equation for determining the depth of the damped (supported) water flow, which is formed during the connection of streams, has been derived.